Kompetensi, Sistem Pengendalian Internal, Locus of Control, dan Pencegahan Fraud Pengelolaan Dana Desa - Puspita, Ni Kadek Mega Cahya; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi; Vol 33 No 2 (2023), 2023)
The aim of the study was to test empirically the influence of village apparatus competence, internal control systems and internal locus of control on fraud prevention in managing village funds. The research was conducted in 23 villages in Gianyar Regency, Bali. The sampling used probability sampling, namely proportionate stratified random sampling and obtained a sample of 66 people. Data were analyzed using multiple linear regression analysis. The findings of the analysis show that village apparatus competence, internal control systems and internal locus of control have a positive influence on preventing fraud in managing village funds. This means that by increasing the competence of village apparatus, implementing an adequate internal control system and supported by a good internal locus of control can improve fraud prevention in managing village funds. Keywords: Fraud; Competence; Internal Control System; Locus of Control.